The current state of infrastructure quality, equipment, and environmental landscape at sports training establishments in specialized schools and sports training centers based on tangible cultural criteria (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
The current state of infrastructure quality, equipment, and environmental landscape at sports training establishments in specialized schools and sports training centers based on tangible cultural criteria